Incidence of Gastric Cancer in Marrakech and Casablanca, Morocco. (21st October 2015) - Smith, Brittney L.; Khouchani, Mouna; Karkouri, Mehdi; Lazenby, Audrey J.; Watkins, Katherine; Tahri, Ali; Benider, Abdel-Latif; Rajaram, Shireen; Soliman, Amr S.
Abstract : Gastric cancer is the fifth most common cancer globally with over 70% of new cases occurring in developing countries. In Morocco, oncologists in Marrakech suspected higher frequency of gastric cancer compared to Casablanca, a city 150 kilometers away. This study calculated age-specific, sex-specific, and total incidence rates of gastric cancer in Marrakech and was compared to the Casablanca population-based cancer registry. Using medical records from Center Hospital University Mohammad VI and reports from 4 main private pathology laboratories in Marrakech, we identified 774 patients for the period 2008–2012. Comparison of rates showed higher age-specific incidence in Marrakech in nearly all age groups for both genders. A higher total incidence in Marrakech than in Casablanca was found with rates of 5.50 and 3.23 per 100, 000, respectively. Incidence was significantly higher among males in Marrakech than males in Casablanca (7.19 and 3.91 per 100, 000, resp.) and females in Marrakech compared to females in Casablanca (3.87 and 2.58 per 100, 000, resp.). Future studies should address possible underestimation of gastric cancer in Marrakech, estimate incidence in other regions of Morocco, and investigate possible risk factors to explain the difference in rates.